SISTEM PENGUPAHAN BURUH KELAPA SAWIT DI KAMPUNG TUMANG KECAMATAN SIAK DALAM PERSPEKTIF EKONOMI ISLAM - Wiwik Indra Mariana; Suci Rahma Sari (Al-Hasyimiyah: Jurnal Ekonomi Syariah, 2025)
This study aims to examine the wage system for oil palm plantation laborers in Tumang Village, Siak District, from an Islamic perspective. The research method used is descriptive qualitative. The subjects of this study are oil palm plantation workers in Tumang Village. The results show that the wage payment system for oil palm plantation laborers in Tumang Village, Siak District, particularly regarding the timing of wage payments, is not in accordance with Islamic teachings, as the wages received are sometimes not in line with the initial agreement or are paid late. However, from the perspective of Islamic economics, the wage system for oil palm plantation laborers in Tumang Village, Siak District can be considered appropriate because the wages provided are commensurate with the work performed. The wage system and the amount of wages given are based on local community customs, so plantation owners do not arbitrarily determine wages. Both parties, before entering into a cooperation agreement, are already aware of the prevailing wage rates in the market